Labour law implications of outsourcing in public sector - Senčur Peček, Darja (Lex localis, 2017)
Employers are increasingly resorting to the. contractual delegation of certain activities to outside contractors. Legal status of employees who previously performed this work with the employer depends mainly on whether there has been the transfer of the undertaking within the meaning of Directive 2001/23/EC. According to case law of the Court of Justice of the EU, in addition to the performance of the same activities, a condition is also the transfer of essential means of work or transition of employees. Since the transition of employees in this case depends on the agreement between the contracting authority and the provider of services, terms of public procurement are very important in this regard. The article addresses the question of the application or non-application of the institution of the transfer of the undertaking in cases of outsourcing in public sector while paying attention to Slovenian and Croatian legislation and to the Directive.
Keywords: delovno pravo; javni sektor; outsourcing; prenos podjetja; public procurement; public sector; termination of employment contract; transfer of undertaking; zunanje izvajanje